Surprising genetic and pathological findings in a patient with giant bilateral periadrenal tumours: PEComas and mutations of PTCH1 in Gorlin-Goltz syndrome. Issue 9 (16th December 2021) - Igaz, Peter; Toth, Geza; Nagy, Peter; Dezső, Katalin; Turai, Peter Istvan; Medvecz, Marta; Wikonkal, Norbert; Huszty, Gergely; Piros, László; Toth, Erika; Bozsik, Aniko; Likó, István; et al.
Abstract : Gorlin-Goltz syndrome (GGS) or nevoid basal cell carcinoma syndrome is a rare tumour-overgrowth syndrome associated with multiple developmental anomalies and a wide variety of tumours. Here, we describe a case of a man aged 23 years with GGS with bilateral giant tumours adjacent to both adrenals that raised the suspicion of malignancy on imaging. Histological analysis of both surgically resected tumours revealed perivascular epitheloid cell tumours (PEComas) that were independent of the adrenals. Exome sequencing of the patient's blood sample revealed a novel germline heterozygous frameshift mutation in the PTCH1 gene. As a second hit, a somatic five nucleotide long deletion in the PTCH1 gene was demonstrated in the tumour DNA of both PEComas. To the best of our knowledge, this is the first report on PEComa in GGS, and this finding also raises the potential relevance of PTCH1 mutations and altered sonic hedgehog signalling in PEComa pathogenesis. The presence of the same somatic mutation in the bilateral tumours might indicate the possibility of a postzygotic somatic mutation that along with the germline mutation of the same gene could represent an intriguing genetic phenomenon (type 2 segmental mosaicism).